Is rheumatoid arthritis a risk factor for oral bisphosphonate-induced osteonecrosis of the jaws? - Neto, Nicolau Conte [UNESP]; Bastos, Alliny de Souza [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Marcantonio, Elcio [UNESP] (Churchill Livingstone, 2011)
Bisphosphonate-related osteonecrosis of the jaws is a relevant side-effect of these drugs that has been generating a great concern through increasing reports, worldwide, of this bone necrosis. Among several BRONJ hypothetical co-factors that could play a role in BRONJ pathogenesis, rheumatoid arthritis (RA) has been included as a relevant risk factor for BRONJ; however, until now the relationship between these diseases has not been fully explained. Thus, the purpose of this paper is to establish hypothetical factors that could link these two diseases, considering mainly inflammatory components and the organism effects of medicines used to treat RA, particularly steroids and methotrexate (MTX). (C) 2011 Elsevier Ltd. All rights reserved.